Institutional environment of entrepreneurial activity through the lens of economic culture - Yu.V. Ushchapovskyi (Проблеми теорії та методології бухгалтерського обліку, контролю і аналізу)
The article focuses on entrepreneurship as an economic entity in the process of evolution of market relations and the emergence of a free individual. Attention is drawn to the fact that the institutionalization of the division of labor is a consequence of the transfer of the subjective functions of the individual to individual social strata and business entities. It is emphasized that the social aspects of entrepreneurship narrow the boundaries of its subjectivity, since the external environment of economic activity sets significant restrictions on the freedom of decision-making. The entrepreneur’s behavior forms and affects the norms and restrictions of economic activity, which creates the prerequisites for its institutionalization. Based on «economic interactions», three levels of economic culture are identified and the place of the culture of entrepreneurship in economic culture is clarified. It is emphasized that the economic culture of entrepreneurship is most consistent with the economic culture of managers and heads of organizations, which applies to a significant number of people who delegated to them their rights in decision-making. Attention is paid to the differences between entrepreneurship and management through the lens of strategic orientation and the organizational structure of entrepreneurial activity. Entrepreneurship is organizationally focused on the use of horizontal informal ties, which provides for the coordination of the actions of independent participants in the process. The norms of political culture significantly affect the implantation of legal norms of economic activity, and is the connecting link between informal restrictions and formal rules in the economy. The Enterprise Institute embodies an innovative economic culture, provides an innovative type of economic growth and contributes to the competitiveness of the national economy.